Paleoceanographic and paleoclimatic reconstruction based on marine palynomorphs in the period 1811–1907 CE in the Magdalena Basin, Baja California Sur, Mexico - Laura Cristina López-Velázquez; Javier Helenes; Juan Gabriel Flores-Trujillo; Ana Carolina Ruiz-Fernández; Joan Albert Sanchez-Cabeza (Ciencias Marinas, 2019)
Biennial variations of marine palynomorph concentrations mirrored oceanographic conditions in the Magdalena Basin, Baja California Sur (Mexico), in the period from 1811 to 1907 (common era, CE), for which the sea surface temperature index (SSTI) showed predominantly negative anomalies. We analyzed 49 samples of laminated sediments taken from a core extracted at a water depth of 520 m. Changes in dinoflagellate assemblages and copepod egg abundances were compared to SSTI records and to El Niño Southern Oscillation (ENSO) and Pacific Decadal Oscillation (PDO) reconstructions. Copepods were the most abundant and showed a significant correlation with SSTI. Among the dinoflagellates, heterotrophs were the most abundant and did not correlate with SSTI. The lowest concentration of autotrophs showed a significant and inverse correlation with SSTI. The canonical correlation analysis also indicated that copepods and autotrophs were modulated by variations in SSTI. Dinoflagellate richness and concentrations and copepod egg concentrations were low, indicating low productivity, and these values coincided with the negative SSTI anomalies. In contrast, the increase in concentrations from 1881 to 1907 CE coincided with positive SSTI anomalies. Also, even when marine palynomorphs showed no significant correlation with either ENSO or PDO, their concentrations increased during age intervals with combined negative conditions (La Niña, negative PDO) and decreased during combined warm conditions (El Niño, positive PDO).